Pengaruh Profitabilitas, Kebijakan Dividen, dan Kepemilikan Manajerial terhadap Nilai Perusahaan Perbankan 2021-2024 - Puja Dwi Ramadhani; Erna Sulistyowati (Forum Kerjasama Pendidikan Tinggi, 2026)
This study explores the dynamics of firm value in the Indonesian banking sector over the period from 2021 to 2024, a crucial post-economic recovery period. The main focus of the analysis lies in the interaction between profitability performance, dividend policy, and governance structure through managerial ownership. Adopting a quantitative methodology, this research processes secondary data sourced from annual financial reports. To ensure the accuracy of the results, sample selection was strictly conducted using the purposive sampling method, yielding 10 banking entities equivalent to 40 data observation units. In order to dissect the influence of these variables, statistical analysis was performed using panel data regression by applying the Random Effect Model (REM), which was selected due to its capability to accommodate variations in characteristics among banking companies during the observation period. Partially, the findings of this research confirm that profitability efficiency acts as the main driver in strengthening firm value (? = 24.930; p = 0.0000), where solid earnings performance is responded to positively by the market. Interestingly, there is an anomaly in the dividend policy which demonstrates a significant negative correlation (? = -0.561; p = 0.0263), a condition that often reflects investor skepticism regarding the company's long-term growth prospects when profits are allocated to dividends rather than reinvestment. Meanwhile, the managerial ownership variable does not show statistical significance (p = 0.4146) in affecting valuation, implying that for market participants in the banking industry, the concentration of shares in the hands of management has not become a crucial signal for market value. However, when these three variables were tested collectively (simultaneously), their predictive power on firm value became highly robust (F = 8.571; p = 0.0002; Adjusted R² = 0.368). The discrepancy in results between the partial and simultaneous tests emphasizes that capital market investors have specific priorities: they tend to position the fundamental capability of banks to generate net profit as the dominant indicator, which is capable of overshadowing the dynamics of dividends and managerial ownership structure in determining their investment decisions. As a main contribution, this study provides strategic guidance for banking management to prioritize reinvestment strategies and strengthen profit fundamentals to maximize shareholder wealth, while also enriching empirical financial literature by providing evidence of anomalous market responses to dividend distribution in the banking sector during the post-economic recovery phase.